Coronavirus Disease 2019 (COVID-19) – An Overview - Bashera, Ariful; Das, Debashish; Faiz, M Abul (Journal of Bangladesh College of Physicians and Surgeons, 2020)
The coronavirus disease 2019 (COVID-19) is now a pandemic with a massive death toll across the world. The knowledge and understanding of this novel coronavirus transmission and pathogenesis are evolving. Although the landscape of vaccine and drug development is changing at an unprecedented pace, currently, there is no specific effective treatment. Proper and timely management of severe and critically ill COVID-19 patients is crucial to reduce deaths in the ongoing pandemic. Ramping up testing capacity alongside a test strategy in place, ensuring adequate resources, i.e., protective gear, O2 supply, ICU facilities are essential requirements in the fight against COVID-19. Infection prevention and control measures at a personal level (e.g., handwashing, wearing masks, proper donning and doffing of personal protective equipment), and at hospital settings (e.g., hospital cleanliness, safe handling, and disposal of waste) are extremely important to reduce the risk of infection. COVID-19 pandemic has caused a global crisis that requires a multidisciplinary response and concerted effort to ensure resilience in health systems. J Bangladesh Coll Phys Surg 2020; 38(0): 84-90